Regional Cortical Thickness Predicts Top Cognitive Performance in the Elderly - Dominguez, Elena Nicole; Stark, Shauna M.; Ren, Yueqi; Corrada, Maria M.; Kawas, Claudia H.; Stark, Craig E. L. (Frontiers in Aging Neuroscience, 2021)
While aging is typically associated with cognitive decline, some individuals are able to diverge from the characteristic downward slope and maintain very high levels of cognitive performance. Prior studies have found that cortical thickness in the cingulate cortex, a region involved in information processing, memory, and attention, distinguish those with exceptional cognitive abilities when compared to their cognitively more typical elderly peers. Others major areas outside of the cingulate, such as the prefrontal cortex & insula, are also key in successful aging well into late age, suggesting that structural properties across a wide range of areas may better explain differences in cognitive abilities. Here, we aim to assess the role of regional cortical thickness, both in the cingulate and the whole brain, in modeling Top Cognitive Performance (TCP), measured by performance in the top 50th percentile of memory & executive function. Using data from National Alzheimer’s Coordinating Center and The 90+ Study, we examined healthy subjects aged 70-100 years old. We found that, while thickness in cingulate regions can model TCP status with some degree of accuracy, a whole- brain, network-level approach out-performed the localist, cingulate models. These findings suggests a need for more network-style approaches and furthers our understanding of neurobiological factors contributing to preserved cognition.